Reductive Functionalization of Amides in Synthesis and for Modification of Bioactive Compounds - Czerwiński, Paweł J.; Furman, Bartłomiej (Frontiers in Chemistry, 2021)
In this review, applications of the amide reductive functionalization methodology for the synthesis and modification of bioactive compounds are covered. A brief summary of the different protocols are presented in the introduction, followed by the synthetic application of these in late-stage functionalization leading to known pharmaceuticals or to their derivatives, including bioisosteres, with potential higher activity as the main axis of the article. The synthetic approach to natural products based on amide reduction is also discussed, however, this is given in a condensed form focusing on recent or as yet unexplored applications due to a number of recently published excellent reviews covering this topic. The aim of this review is to illustrate the potential of reductive functionalization of amides as an elegant and useful tool in the synthesis of bioactive compounds and inspire further work in this field.